2014
DOI: 10.1093/nar/gku464
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplex conformation and dynamics are determined by loop length and sequence

Abstract: The quadruplex forming G-rich sequences are unevenly distributed throughout the human genome. Their enrichment in oncogenic promoters and telomeres has generated interest in targeting G-quadruplex (GQ) for an anticancer therapy. Here, we present a quantitative analysis on the conformations and dynamics of GQ forming sequences measured by single molecule fluorescence. Additionally, we relate these properties to GQ targeting ligands and G4 resolvase 1 (G4R1) protein binding. Our result shows that both the loop (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
190
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(222 citation statements)
references
References 54 publications
(71 reference statements)
18
190
0
Order By: Relevance
“…3). The loop length and sequence contribute to the conformation of the G-quadruplex [15]. Replacement of the central G by A or I also alter the overall structure (Supporting information S2), particularly the lower G-quartet.…”
Section: Structure Of the G-quadruplex With X = G A Or Imentioning
confidence: 99%
See 3 more Smart Citations
“…3). The loop length and sequence contribute to the conformation of the G-quadruplex [15]. Replacement of the central G by A or I also alter the overall structure (Supporting information S2), particularly the lower G-quartet.…”
Section: Structure Of the G-quadruplex With X = G A Or Imentioning
confidence: 99%
“…These monovalent cationic ions interact with the carbonyl group of the G bases. A variety of structures depending on the number of G-quartet, nature of loops and central cation have been reported [8][9][10][11][12][13][14][15]. For example, an early NMR study of a thrombin-binding aptamer, 5′G 2 T 2 G 2 TGTG 2 T 2 G 2 , showed that this DNA adopts a highly compact, high symmetrical structure that consist of tetrads of G base pairs and three loops ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much less is known however about the effect on the quadruplex structure of such lesions of the loops [40e42]. Current knowledge is that the sequence and length of loop determine primarily the quadruplex folding, which of course, influences its stability [43,44]. A recent study on single-molecule mechanical unfolding of a three-tetrad telomeric G-quadruplex however concluded that the loop interactions contributed more to G-quadruplex stability than the stacking of G-tetrads [45].…”
Section: Introductionmentioning
confidence: 99%